Pengembangan Kemampuan Kognitif Dalam Mengklasifikasikan Benda Menggunakan Model Project Based Learning Berbantuan Papan Flannel - Fadilah, Nadia; Purwanti, Ratna; Suriansyah, Ahmad (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The problem in this study is the low activity and cognitive development of children in classifying objects based on shape, color and size in group B of Hidayatullah Barito Kuala Kindergarten. The purpose of this study was to describe teacher activities, children's activities, and analyze the results of children's cognitive development in classifying objects based on shape, color and size. This approach uses a qualitative approach and the type of research is Classroom Action Research (CAR). with 4 meetings. The results showed that teacher activity increased from a score of 17 (category "Quite Good") in meeting 1 to 27 (category "Very Good") in meeting 4. Children's activity increased from 13% (category "Less Active") in meeting 1 to 94% (category "Very Active") in meeting 4. Children's cognitive development in classifying objects increased from 54% in meeting 1 to 100% in meeting 4. Based on the results of the study, it can be concluded that through the Project Based Learning Model, the Demonstration Method with Flannel Board Media can increase teacher activity, children's activity, and children's cognitive development results in Classifying Objects Based on Shape, Color and Size